Ecological infrastructure planning corridor resource landscape management approach of Angat River basin - Danao, Madonna P. (Quezon City College of Architecture, University of the Philippines Diliman, 2014)
Most of today's existing landscape is already fragmented and urbanized. Planners are developing approaches and concepts to the further impede the fragmentation and urbanization our environment faces to achieve sustainable landscape planning. Ecological infrastructure planning represents a strategic approach to natural and physical resource conservation that combines the efforts of previous conservation planning methodologies and practices into a systematic framework that encompasses larger and broader planning goals, particularly in river corridors. This research emphasizes ecological infrastructure planning approach as a viable approach to sustain air, land and water resources to contribute to health and quality of life in river corridors such as Angat River basin. Ecological infrastructure planning approach involves decision-making and actions on interconnecting networks of waterways, wetlands, woodlands, wildlife habitats and other natural areas; green ways, parks, and other conservation lands; working farms, ranches and forests, and wilderness and other open spaces to support native species, maintain natural ecological processes. This paper aims to provide a comprehensive analysis and description and evaluation of ecological infrastructure usin biotope mapping of the Angat river corridor. It also applies landscape management through ecological infrastructure approach in the planning process. Thus, will lead to the creation of an ecological management map and strategies as guide in sustainable development of urbanizing Angat river corridor. Strategies recommended should be adopted to ensure the sustainable development of the Angat River basin corridor resources. Following the strategies for each biotope and the government's program on watershed management that involves DENR, NIA and NPC plus the LGUs will ensure the protection of the forest and the river basin from unsustainable practices in the river basin. It is also recommended that landscape architects should take the lead in the ecological planning particularly in planning urban corridors.
Thesis (Master of Tropical Landscape Architecture)--University of the Philippines Diliman